Implementation of Joint Replenishment Inventory Model with Quantity Discounts. - Rajendran, Keerthana (2013)
The purpose of this dissertation is to investigate the feasibility of implementing joint replenishment inventory models to help Palmer and Harvey manage their soft drinks inventory levels. The inventory management decisions involving Coca Cola Enterprise (CCE) and their wholesale partner Palmer and Harvey is an interesting case to investigate taking into consideration the two quantity discount models proposed by CCE. Analysis of the available input data is carried out through simulations to decide on the appropriate model to suit P&H’s business needs. Choice of the ideal inventory model is made through a comparative study of three models viz; Economic Order Quantity model, the simplest of the inventory models, the Modified EOQ approach and finally the Joint replenishment Model. The purpose of these simulations is to analyse the results of the models considered and to facilitate their comprehension and comparison to select the appropriate inventory management alternative for Palmer and Harvey that will help them benefit from the discounts offered by Coca-Cola Enterprise at minimum inventory costs. The performance of these models are measured against certain key indicators like the average inventory level, service level achieved and the total relevant cost in order to access the effectiveness and efficiency of the models in comparison to the inventory system currently implemented by P&H. A brief introduction to the problem at hand is presented before carrying out a detailed literature review on concepts of inventory management, its importance and the various inventory models in practise with primary focus on the principles of Joint Replenishment models and theories surrounding the benefits of quantity discounts in managing inventory. The literature review is followed up by a thorough study on the methodology adopted to implement the inventory models through Excel simulations and organisation of the results for decision making purposes. An overview of LINGO, a software tool used to solve integer programming problems is also presented to aid the determination of order quantity under Joint Replenishment system. A final analysis of the results obtained is carried out and the findings are presented and recommendations are made as a conclusion of the work.